Optimization of Organizational Performance by Utilization of AI for Strategic Management Insights - Loso Judijanto; Asfahani Asfahani; Syamsul Muqorrobin; Nova Krisnawati (Edujavare Publishing, 2025)
In response to the complexities of modern markets, organizations are increasingly turning to Artificial Intelligence (AI) as a transformative tool for enhancing strategic decision-making and organizational performance. This study investigates the impact of AI utilization on optimizing organizational performance within strategic management. A qualitative research method was employed, utilizing semi-structured interviews to gather insights from key organizational informants. The findings highlight the significant role of organizational culture, leadership support, and collaborative approaches in maximizing AI's potential for agility, informed decision-making, and competitive advantage. The analysis contributes to a deeper understanding of AI's implications for strategic management and underscores the importance of holistic approaches in leveraging AI for sustained performance enhancement.